2022
DOI: 10.1002/chem.202202921
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Activity Relationships in Nucleic‐Acid‐Templated Vectors Based on Peptidic Dynamic Covalent Polymers

Abstract: The use of nucleic acids as templates, which can trigger the self-assembly of their own vectors represent an emerging, simple and versatile, approach toward the selffabrication of tailored nucleic acids delivery vectors. However, the structure-activity relationships governing this complex templated self-assembly process that accompanies the complexation of nucleic acids remains poorly understood. Herein, the class of arginine-rich dynamic covalent polymers (DCPs) composed of different monomers varying the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Using complementary modified cationic peptides flanked with a hydrazide C‐terminus, oxyamine N‐terminus, and complementary bisaldehyde peptides ( Ox‐Arg 3 ‐Hyd and BisAld , Figure 5C), we showed that a siRNA‐templated polymerization takes place through the in situ formation of acylhydrazone and oxime bonds, leading, over the course of a 16 hours incubation, to neutral polyplex nanoparticles (ζ potential 1.3 mV) [57] . Increasing the number of cationic groups in monomers was found to accelerate the process which is complete within 30 minutes incubation with trisarginine building blocks [58] . This phenomenon most likely originates from an increased residence time of the cationic monomers onto nucleic acid when their positive charges are increased.…”
Section: Smart Polymers For Gene Deliverymentioning
confidence: 89%
See 1 more Smart Citation
“…Using complementary modified cationic peptides flanked with a hydrazide C‐terminus, oxyamine N‐terminus, and complementary bisaldehyde peptides ( Ox‐Arg 3 ‐Hyd and BisAld , Figure 5C), we showed that a siRNA‐templated polymerization takes place through the in situ formation of acylhydrazone and oxime bonds, leading, over the course of a 16 hours incubation, to neutral polyplex nanoparticles (ζ potential 1.3 mV) [57] . Increasing the number of cationic groups in monomers was found to accelerate the process which is complete within 30 minutes incubation with trisarginine building blocks [58] . This phenomenon most likely originates from an increased residence time of the cationic monomers onto nucleic acid when their positive charges are increased.…”
Section: Smart Polymers For Gene Deliverymentioning
confidence: 89%
“…[57] Increasing the number of cationic groups in monomers was found to accelerate the process which is complete within 30 minutes incubation with trisarginine building blocks. [58] This phenomenon most likely originates from an increased residence time of the cationic monomers onto nucleic acid when their positive charges are increased.…”
Section: Smart Polymers For Gene Deliverymentioning
confidence: 99%
“…Moreover, by incorporating fluorescent moieties into the DCP sequence, they have also paved the way toward the development of optical probes for nucleic acids, for example, to monitor the delivery of a specific functional NA [23] . In their latest work, the templated effect of different nucleic acids ranging from short siRNA to longer DNA (ctDNA, pDNA), on the formation of their peptide‐based DCPs was investigated, which represent an appealing strategy that would enable NA to select their own vector [24] …”
Section: Creating Dynamic Peptide‐like Bondsmentioning
confidence: 99%
“…[23] In their latest work, the templated effect of different nucleic acids ranging from short siRNA to longer DNA (ctDNA, pDNA), on the formation of their peptide-based DCPs was investigated, which represent an appealing strategy that would enable NA to select their own vector. [24] Lynn and co-workers have reported a template-directed reversible amine/aldehyde condensation, for the assembly of peptide-like polymers into a dynamic chemical network capable of multiple-phase transition that culminates in prion-like crossβ-architecture (Figure 2e). [25] To do so, peptide scaffolds made of two or three amino acids were synthesized bearing an aldehyde at their C-terminal side, i. e. H-Asn-Phe-CHO and H-Asn-Phe-Phe-CHO.…”
Section: C=n-type Peptide Bonds Surrogatementioning
confidence: 99%
“…In addition, the potential of DCvC for the in situ optimization of polymeric gene vectors using dynamic covalent libraries has remained largely unexplored. 35 Herein, we describe a highly adaptable gene delivery platform using a polymeric boronic acid that is activated in the presence of pDNA by the addition of cationic catechols (Figure 1). The fast and strong boronate ester bonding in H 2 O affords cationic dynamic polyboronates able to complex pDNA in situ to afford polyplexes that, without further manipulation, efficiently transfect cells.…”
Section: ■ Introductionmentioning
confidence: 99%